Gen Z Smartphone User: The Effect Of Mobile Marketing On Actual Behaviors - Makarim Makarim; Zakky Fahma Auliya (Profesional Muda Cendekia Publishing, 2020)
The development of technology has become an integral part of changing people's behavior. Generation z is a group of individuals who are very close to technology. In Theory of Reasoned Action, behavior variables are influenced by attitudes, subjective norms and the desire to behave. In this study, it focuses on the influence ofinitiatives mobile marketing that have an influence on behavioral intentions, then intentions and subjective norms have an influence on the desire to behave and the desire to behave has an influence on actual behavior. The above research was conducted on generation Z in the city of Surakarta with an age range of 15-24 years. With the number of samples used were 100 respondents. The samples were determined using purposive sampling and the data collection method used a questionnaire. This study uses simple linear regression analysis while the tools used in processing the IBM SPSSdata Statistic 22. The results show a significant influence because it is caused by thevariable mobile marketing on attitude, then attitude and subjective norm have a positive significant effect on intention behavior. Then intention behavior has a significant positive effect on actual behavior.